Pengaruh Financial Literacy, Financial Technology, Financial Self-Efficacy, Income, Life Style, dan Emotional Intelligence terhadap Financial Management Bahavior pada Remaja di Kabupaten Ponorogo - Defrina Rizqi Lathiifah; Achmad Kautsar (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study uses quantitative research to determine the effect of financial literacy, financial technology, financial self-efficacy, income, lifestyle, and emotional intelligence on financial management behaviour. The subject for this research population was Teenagers at Ponorogo Regency. There is 2020 respondent as the sample of this research using non-probability purposive sampling. There are 220 respondents as the research sample obtained through non-probability and purposive sampling. The data analysis technique in this study used multiple linear regression. This research result indicates that financial literacy, financial technology, financial self-efficacy, income, lifestyle, and emotional intelligence significantly affect financial management behaviour. Teenagers are expected to be aware of the need for financial literacy and increase financial literacy that focuses on investment and insurance so that in the future, they will be able to manage their finances better. They also need to encourage self-confidence, especially in their financial management abilities, so that youth are wiser and more responsible in managing their finances. Indirectly, the psychological condition of a teenager can affect the increase in emotional intelligence and lifestyle of adolescents in Ponorogo Regency.